Extraction of potassium from microcline by chlorination - Orosco, Roberto Pablo (2019)
A pyrometallurgical route for the extraction of potassium from microcline was investigated. The reagents used were microcline, calcite and chlorine gas. Isothermal and non-isothermal chlorination assays were performed using experimental equipment adapted for working in corrosive atmospheres. The effects of temperature and reaction time on the chlorination reaction of the microcline-calcite mixture were studied. The reaction mechanism was also investigated. The techniques used to characterize reagents and products were thermogravimetric analysis (TGA), X-ray diffraction (XRD), scanning electron microscopy (SEM), and electron probe microanalysis (EPMA). The experimental results showed that the extraction of potassium in the form of KCl begins at 700 °C for 15 min. Anorthite also starts to be produced under these conditions. The optimum conditions for quantitative extraction of potassium and selective formation of anorthite were 900 °C for 60 min.